2014
DOI: 10.11591/eecsi.v1.357
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Discovery Database (KDD)-Data Mining Application in Transportation

Abstract: In this paper, an understanding and a review of data mining (DM) development and its applications in logistics and specifically transportation are highlighted. Even though data mining has been successful in becoming a major component of various business processes and applications, the benefits and real-world expectations are very important to consider. It is also surprising to note that very little is known to date about the usefulness of applying data mining in transport related research. From the literature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Classical statistics have limitations for performing large amounts of data analysis or complex relationships between data variables. The solution for this problem and its limitations is to develop computerbased data analysis tools with more excellent capabilities and are automatic [20]. With the development of semi-automatic approaches in various fields of science, in recent decades, there has been an increase and across disciplines, such as AI, statistics, and information systems.…”
Section: Data Miningmentioning
confidence: 99%
“…Classical statistics have limitations for performing large amounts of data analysis or complex relationships between data variables. The solution for this problem and its limitations is to develop computerbased data analysis tools with more excellent capabilities and are automatic [20]. With the development of semi-automatic approaches in various fields of science, in recent decades, there has been an increase and across disciplines, such as AI, statistics, and information systems.…”
Section: Data Miningmentioning
confidence: 99%
“…Data mining is a process to explore the excess value of information that was not previously known to exist in a database. The patterns that are very useful and have more value than the data contained in the database are obtained by recognizing the information obtained [11]. From the explanation above it can be concluded that data mining is a step of analyzing the process of knowledge discovery in the database.…”
Section: Issn: 2252-8938mentioning
confidence: 99%
“…The analysis of the current international practice of the subject area shows the following global factors that have a significant and permanent impact on the information management of modern logistics 3PL (Fauziah Abdul Rahman et al, 2014):…”
Section: Introductionmentioning
confidence: 99%